Essential oil and antioxidant activity of the aerial parts of coriander (Coriandrum sativum L.) cultivated in Ethiopia - Assefa, Mekides; Ele Yaya, Estifanos; Singh Chandravanshi, Bhagwan; Assefa Sisay, Melaku (Ethiopian Journal of Science and Technology, 2025)
Coriander (Coriandrum sativum L.) is an annual herbaceous plant which is used as spice. It is widely cultivated throughout the world for its essential oils. The percent composition of commercial essential oils is highly variable due to the effect of geographical origin. In the present investigation, the chemical constituents of the essential oils obtained from the aerial parts of the plant collected from three different areas of Ethiopia were determined by gas chromatography-mass spectrometry. The number of compounds identified in the essential oils of the plants from Jimma was 47, from Wolaita Sodo 21, and from Sululta 19. The major components of the essential oils were found to be decanal and (E)-2-decenal. The methanol extract of coriander aerial parts exhibited DPPH anti-oxidant activities in the range 91.1-92.3% at 500 µg/mL. Therefore, coriander aerial parts can safely be used for food flavoring and food preservation.